The Effect of Public Interest Reporting Obligations on Taxation with E-Filling System - Niati, Asih; Tunjungsari, Ratna (Economics and Business Solutions Journal, 2017)
One of the economic policy packages issued to stimulate the economy in this country is tax, which is one of resource that is needed to finance the state s economy. In 2015, the amount of revenue from personal income taxpayer was very low and still depended on the corporate income taxpayer. As a result, this dependence will affect the nation s economic fluctuation. Therefore, the government in 2016 will focus on personal income taxpayers. The fact found in the field is that people have not using the E-Filling. The population in this study was people in the Tegalsari Sub-District of Candisari District, Semarang who have aTINand the number of sample is 82 respondents.The results showed that based on simultaneous test, it is found that the perceived usefulness, taxpayer s compliance, Quality of Information and Technology, Quality of Service variables simultaneously affect the taxpayer s interest in using the E-Filling. Based on the partial test, it is noted that the perceived usefulness and Information Technology Quality variables do not significantly affect taxpayer readability in using E Filling to report their tax obligations while Taxpayer s compliance and quality of service variables significantly influence the taxpayer's interest in using the E -Filling to report their tax obligations.